Effect of different types of heat processing on chemical changes in tuna - Stephen, Nimish Mol (Springer-Verlag, 2010)
The chemical changes in skipjack tuna (Katsuwonus pelamis) subjected to cooking, frying, canning and microwave heating were studied. Raw tuna contained an unusual fatty acid C16:3 in high proportion (29.3%) followed by C18:2, C24:1, C16:0 and C18:3. Health beneficial fatty acids, eicosapentaenoic acid (EPA) (1.67%) and docosahexaenoic acid (DHA) (2.50%), were quite low with ω-3/ω-6 ratio 0.28. The total saturated fatty acids suffered major loss in fried (70%) and canned tuna (40%) due to loss of C16:0, C14:0 and C22:0. The monounsaturated fatty acids content increased (38%) in cooked and microwave heated tuna due to C24:1. The polyunsaturated fatty acids content increased in fried (50%) and canned (25%) tuna due to the uptake of frying and filling oil, respectively during processing. The loss of health beneficial ω-3 fatty acids, EPA and DHA were minimum in cooked tuna followed by microwave heated tuna. Canning totally destroyed these fatty acids. In fried tuna, the losses of EPA and DHA were 70 and 85%, respectively. Thiobarbituric acid — reactive substances values increased in heat processed tuna. Cholesterol increased in canned and microwave heated tuna but not in cooked tuna. Reduction of cholesterol in fried tuna was due to its migration into frying oil. This study indicated that cooking and microwave heating are the better processing methods to retain the health beneficial ω-3 fatty acids in comparison to frying and canning.